Nebivolol Mitigate the Hepatic Expression Level of Inducible and Endothelial Nitric Oxide Synthase in Tamoxifen-Induced Oxido-Inflammatory Changes in Female Rats - Noor Ahmed Hammadi; Yassir Mustafa Kamal Al Mulla Hummadi; Huda Jaber Waheed (Iraqi Journal of Pharmaceutical Sciences, 2025)
Liver injury can arise post-exposure to drugs or their metabolites, herbal and dietary supplements. Tamoxifen is a famous drug used in breast cancer treatment. Long-term tamoxifen treatment has been associated with the development of hepatotoxicity. Oxidative stress, fatty changes, and inflammation are the major implicated mechanisms contributing to tamoxifen hepatotoxicity including the iNOS-mediated inflammatory pathway in addition to standard hepatotoxicity biomarkers like alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Nebivolol is a third-generation selective beta1-adrenergic receptor blocker with vasodilator characteristics with significant antioxidant activity. The present study was designed to investigate the possible protective role of nebivolol against rat hepatotoxicity induced by tamoxifen. Rats utilized in this study were randomized into 5 groups (6 rats per group); Group 1- (Control) rats received distilled water (5mL/kg b.w. orally) for 14 consecutive days. Group 2- Rats received tamoxifen (75mg/kg b.w., orally) on days 13,14 only. Group 3- Rats received Nebivolol (5 mg/kg b.w., orally for 14 consecutive days) and tamoxifen (75mg/kg b.w., orally) on days 13,14 only. Group 4- Rats received Nebivolol (8 mg/kg b.w., orally for 14 consecutive days) and tamoxifen (75mg/kg b.w., orally) on days 13,14 only. Group 5- Rats received Nebivolol (8 mg/kg b.w., orally for 14 consecutive days) and tamoxifen (75mg/kg b.w., orally) on days 13,14 only. pre-administration of nebivolol at different doses with tamoxifen showed significant downregulation (P<0.05) in hepatic AST, ALT, and iNOS with overexpression of eNOS compared to corresponding levels in the tamoxifen-only treated group. In conclusion, this study demonstrated that pre-administration of nebivolol in different doses with tamoxifen resulted in attenuation of its hepatotoxicity by the utilization of selected parameters.